SOSIALISASI SISTEM PENGENDALIAN REKAM MEDIS TERKOMPUTERISASI DI RUMAH SAKIT AWAL BROS BATAM - Pradita, Riska; Kusumo, Retno; Rahmawati (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
In the era of electronic medical records, it is important to computerize the control system for medical record files to facilitate recording, borrowing, returning, controlling, and managing medical records. By implementing a computerized system, it becomes easier for officers to record, borrow, return, control, and locate medical record files that are taken out of storage. The computerized system eliminates the need for manual record-keeping and ensures proper control and management of medical records, reducing the risk of loss and misfiling. This study focuses on observations made at the Awal Bros Hospital Medical Record Unit in Batam, where missfile incidents occurred frequently, leading to duplicate medical record files and unreliable patient data, as well as wastage of forms. The objective of this research is to raise awareness among officers about a desktop-based computerized medical record control system, with the aim of reducing the loss of medical record documents and occurrences of misfiling. The community service activity was conducted at Awal Bros Batam Hospital in May 2023 and involved lectures and question-and-answer sessions with IT officers and medical record personnel. The outcome of this activity was the socialization of a prototype desktop-based computerized medical record control system to be implemented for storing and retrieving patient medical record files at Awal Bros Hospital Batam. An evaluation of the system was obtained from the participants after the socialization. In conclusion, this community service initiative successfully increased the knowledge of officers in the Medical Record Unit, particularly in the Filing section, regarding the control of computerized medical records.